Occurrence of arbuscular mycorrhizal fungi in the roots of two grapevine cultivars in response to bioproducts - Paszt, Lidia Sas; Głuszek, Sławomir; Derkowska, Edyta; Sumorok, Beata; Lisek, Jerzy; Trzciński, Paweł; Lisek, Anna; Frąc, Mateusz; Sitarek, Mirosław; Przybył, Michał (South African Journal of Enology and Viticulture, 2019)
The aim of this study was to determine the influence of different bioproducts on the occurrence of arbuscular mycorrhizal fungi (AMF) in the roots of ‘Solaris’ and ‘Regent’ grapevine cultivars. The following bioproducts were used, alone or with mineral fertilization (NPK): Ausma, Bioilsa, manure and BF Ekomix. The highest mycorrhizal frequency was recorded in the roots of ‘Solaris’ after applying the bioproduct Ausma. For the ‘Regent’ cultivar, the highest mycorrhizal frequency was found in the plants treated with Ausma, BF Ekomix and manure. Colonization of grapevine roots by AM fungi was limited by mineral fertilization. After the combined use of bioproducts and mineral fertilizers, there was observed a tendency for minimized negative effect of mineral fertilization on the formation of arbuscular mycorrhizal fungi.